Laws, Subdivisions and Agricultural Colonies: Regulation Mechanisms in Colonization Processes. Colombia and Chile (1920-1950); [Leyes, Parcelaciones y Colonias Agrícolas: Mecanismos de Regulación en Los Procesos de Colonización. Colombia y Chile (1920-1950)*] - Pinto-Vallejos, J; Henao-Holguin, D (Universidad Austral de Chile, 2023)
This paper analyzes the mechanisms of State intervention in terms of colonization towards the internal agricultural frontier areas in two countries: Colombia and Chile. This preliminary study proposes that, to appease rural confusion, both States regulated in a similar way: they installed colonization policies through laws that sought to regulate relations between the State and individuals; and, in parallel, also agricultural colonies and the subdivisions of large properties. For the analysis, we mainly resorted to official publications of the Ministry of Industries, the Ministry of Agriculture, and the Ministry of National Economy, in the case of Colombia. In the case of Chile, reports of the office of Agricultural Settlement and some theses that analyze the formation of the Ministry of Lands and Colonization were reviewed. In both cases, enacted legislation on the occupation of public lands was examined. © 2023, Universidad Austral de Chile. All rights reserved.